Thin Central Corneal Thickness May Be a Risk Factor for Myopia Progression in Children - Peng Zhou; Dan-Dan Wang; Lei Fan; Lin Yang; Ming-Wei Zhao (Journal of Ophthalmology)
Purpose. This study investigated the correlation between corneal biomechanical parameters and the speed of myopia progression. Methods. This is a retrospective, multicenter study. Both Chinese and Caucasian children were involved. The follow-up time was at least 12 months. Ocular biometry data including the central corneal thickness (CCT), axial length (AL), corneal keratometry (K), anterior chamber depth (ACD), white-to-white (WTW) distance, and pupil size (PS) were measured. The age of onset, speed of progression of spherical equivalent (SE), and speed of AL elongation were calculated. Data were analyzed using the R programming language. Results. This study comprised 306 eyes of 153 myopic children. 122 children were Chinese, and 31 children were Caucasian. The myopia progression was faster in Chinese children than that in the Caucasian group in both SE progression speed and AL elongation speed. The CCT was negatively correlated with the SE speed of progression (correlation coefficient, R = −0.65, and p=7.25×10−38) and AL speed (R = −0.47 and p=1.62×10−18). CCT was positively correlated with the age of onset (R = 0.35 and p=4.53×10−10). No significant correlation (R > 0.3 and p<0.01) was found between other ocular biometries (K, ACD, WTW, and PS) and the onset and speed of the progression of myopia. The same trends were found in both Chinese and Caucasian children and in both the right eye and left eye. Conclusion. CCT was negatively correlated with myopia (SE) progression speed and AL elongation speed. Thin CCT may be associated with faster myopia progression.